Hypothyroidism: Cardiovascular Endpoints of Thyroid Hormone Replacement - Stamatouli, Angeliki; Bedoya, Pablo; Yavuz, Sahzene (Frontiers in Endocrinology, 2020)
Hypothyroidism presents in a wide biochemical and clinical spectrum from Subclinical Hypothyroidism (SH) to Overt Hypothyroidism (OH) and myxedema coma. It is the most common endocrine disorder after diabetes and although standard treatment with Levothyroxine (L-T4) replacement is established as monotherapy, multiple symptoms remain unresolved despite maintaining a normal TSH. This led to multiple trials with combination treatment [Levothyroxine (L-T4) / Liothyronine (L-T3)] over the last couple decades 1. In a patient with intact thyroid gland, since symptoms of inadequate or lack of thyroid hormones are mostly non-specific, biochemical testing is the main diagnostic tool after excluding physiologic and/or testing interferences. Typical signs and symptoms of hypothyroidism are correlated with the severity and duration of the disease, but also associated with patient’s age, sex, other comorbidities and the etiology of hypothyroidism. Classic clinical findings in overt to severe hypothyroidism include: reduced deep tendon reflexes, skin changes, weight gain, reduced basic metabolic rate, cognitive dysfunction, and even hypothermia in advanced cases. While it is common to observe these clinical indices in moderate to severe cases, assessment could be challenging if alterations in the thyroid hormone levels are subtle. Major areas of interest of thyroid hormone action, including energy expenditure, body weight, and quality of life parameters are addressed in detail elsewhere in this issue. In this brief review we focused on following clinical indices: the effect of thyroid hormone replacement on lipid panel; carotid intima-media thickness, blood pressure, heart failure; and briefly on deep tendon reflexes and peripheral neuropathy.